Supply chain management practice in Eskayef Pharmaceuticals Limited - Chowdhury, Md. Fahad Nazmul (Brac University, 2021)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2021.